Indigo from Indigofera spp.: Historical and Cultural Overview - Pamela Moon; Yuncong Li; Geoffrey Meru; Wagner Vendrame; Terence Molnar; Xingbo Wu (EDIS, 2024)
This EDIS publication is to introduce indigo as a new economic crop in south Florida. It highlights the historical and cultural background, including identification and distribution, uses, and history of indigo. The information included in this publication could be of interest to researchers, students, extension agents, growers, the dye industry, and the public.